More mushrooms a brand and product development for locally grown oyster mushrooms (Pleurotus ostreatus) among individuals aged 22-30 in Metro Manila as a healthy and sustainable ingredient to support local farmers - Uy, Jessica Riana T.S
The Department of Agriculture launched the Community-Based Mushroom Production program in 2013 to teach farmers from local communities how to cultivate mushrooms using by-products such as rice straw and sawdust. This program aimed to provide farmers with an alternative source of income and also address food security issues as mushrooms can be grown all-year round and are enclosed in mushroom houses, that are less predisposed to the destruction of natural calamities.